-2w=w+12

Simple and best practice solution for -2w=w+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2w=w+12 equation:


-2w=w+12

We simplify the equation to the form, which is simple to understand
-2w=w+12

We move all terms containing w to the left and all other terms to the right.
-2w-1w=+12

We simplify left and right side of the equation.
-3w=+12

We divide both sides of the equation by -3 to get w.
w=-4

See similar equations:

| Rx=(400+20x)(90-1x) | | 42+p=95 | | 14s-20= | | 5n-12=n+18+9n | | 2(x+3)(x+8)= | | Rx=(400+20x)(90+-1x) | | -8+3(2p-4)+10p= | | y*.3=2.5 | | -2(4+3c)-8= | | 12=z | | (4+u)(5u-2)=0 | | 5x-20=3x+15 | | 9y^2+66y+122=0 | | x*.3=2.5 | | 10a+3(a+2)= | | (2v-7)(5-v)=0 | | 5(x+7)+4x^2=(x+5)(x+7) | | 3sin(x)+2cos(x)=0 | | 10x+[2+8x]=4 | | 4x^3-2xy= | | 2.5=11.50 | | 28=8+2x | | -2t-5= | | -53+12X=115 | | 9x-2[x+4]=34 | | Ln(4x-7)=ln(x+5) | | -63=-27-3X | | y+5.8=1.34 | | x+(-12)=112 | | (h^3-2h)+(3h^2+4h)-2h^3= | | 4y=6x-4 | | 100-5p=-20+7p |

Equations solver categories